(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: In any beverage, human tooth enamel dissociates into its ionic products at a threshold pH of beverage <5.5. This study was done to illustrate and compare the demineralization level of enamel after exposure to alcoholic (beer, wine, distilled spirit) and non-alcoholic (carbonated beverage, apple cider vinegar, commercial fruit juice) beverages. Methods: Prior to starting this quasi-experimental study of beverage exposure, buccal surface of enamel was scanned under scanning electron microscope to examine the existing score of enamel samples. Twenty-four non-demineralized samples were randomly flushed with attributed beverage and saliva simultaneously for three minutes by a digital automatic flusher. Samples were further scanned under scanning electron microscope after 30 exposures. Results: pH levels of all beverages were <5.5. After exposure to beverages, all samples were demineralized and 66.6% of samples had the demineralization score of 3. Demineralization score of 2 was observed in 33.3% of samples. The demineralization mean score in non-alcoholic beverages was 3.0 compared to alcoholic beverages 2.3 (P=0.02). Conclusion: All tested beverages had potential to demineralize the enamel structure. The enamel demineralization capacity of non-alcoholic beverages was higher compared to alcoholic beverages. The demineralization capacity of beverages is inversely proportional to their pH.